A realist systematic review of stigma reduction interventions for HIV prevention and care continuum outcomes among men who have sex with men. (July 2020) - Dunbar, Willy; Labat, Aline; Raccurt, Christian; Sohler, Nancy; Pape, Jean William; Maulet, Nathalie; Coppieters, Yves
While stigma associated with human immunodeficiency virus (HIV) infection among men who have sex with men (MSM) is well recognized, there remains relatively limited intervention data on effective stigma reduction strategies. This systematic review was conducted to highlight the mechanisms through which sexual and HIV stigma is reduced in relation to HIV prevention and care engagement. Search of PubMed and Scopus resulted in 11 tested interventions to include in our preliminary model constructed from programme frameworks and recommendations. We refined the preliminary programme theory to identify whether, why, or how mitigation strategies produce observed outcomes. Our review showed that the interventions produced stigma reduction through three groups of mechanisms: (1) Self-acceptance, leadership, and motivational activation for behaviour change from intrapersonal strategies, such as education and mobile health strategies, which intervene on internalized and anticipated stigma; (2) socialization, knowledge sharing, and social empowerment from interpersonal strategies, such as peer support and training for care providers; and (3) community introspection, self-reflection, and humanistic activation from structural strategies such as community leaders' sensitization, which intervene on both anticipated and enacted stigma. Interventions mechanisms act complementarily and can be activated in different contexts in which MSM exposed to and infected with HIV are living.